2018
DOI: 10.1177/0162643418780496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Interview Article Writing Intervention Using Class-wide SNS on Writing Abilities and Self-Esteem of Students With Intellectual Disabilities and Peers’ Attitudes

Abstract: This study was to investigate the effects of a process-based approach to writing interview articles using class-wide social network site (SNS) on the writing abilities and self-esteem of middle school students with intellectual disabilities. It also aimed at investigating these effects on attitudes of the students’ peers who were interviewed. A multiple probe baseline design across participants was employed to assess the writing abilities of three students with intellectual disabilities. A one-group pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Although no meta-analyses have been conducted, several systematic reviews have identified direct instruction, response prompting, and strategy instruction as effective instructional techniques for teaching writing to students with IDD (e.g., Asaro-Saddler, 2016; Joseph & Konrad, 2009; Pennington et al, 2011; Pennington & Delano, 2012; Rogers & Graham, 2008). Self-regulated strategy development (SRSD) has been the most well-researched and appears to be the most effective method of promoting independence across numerous writing skills (Joseph & Konrad, 2009; Rogers & Graham, 2008).…”
Section: Prior Reviews On Writing Interventions For Students With Iddmentioning
confidence: 99%
See 3 more Smart Citations
“…Although no meta-analyses have been conducted, several systematic reviews have identified direct instruction, response prompting, and strategy instruction as effective instructional techniques for teaching writing to students with IDD (e.g., Asaro-Saddler, 2016; Joseph & Konrad, 2009; Pennington et al, 2011; Pennington & Delano, 2012; Rogers & Graham, 2008). Self-regulated strategy development (SRSD) has been the most well-researched and appears to be the most effective method of promoting independence across numerous writing skills (Joseph & Konrad, 2009; Rogers & Graham, 2008).…”
Section: Prior Reviews On Writing Interventions For Students With Iddmentioning
confidence: 99%
“…Although no meta-analyses have been conducted, several systematic reviews have identified direct instruction, response prompting, and strategy instruction as effective instructional techniques for teaching writing to students with IDD (e.g., Asaro-Saddler, 2016; Joseph & Konrad, 2009; Pennington et al, 2011; Pennington & Delano, 2012; Rogers & Graham, 2008). Self-regulated strategy development (SRSD) has been the most well-researched and appears to be the most effective method of promoting independence across numerous writing skills (Joseph & Konrad, 2009; Rogers & Graham, 2008). SRSD is a specific six-stage instructional approach that typically uses a criterion-based performance, requiring students to master a specific—usually mnemonic—strategy (e.g., Pick my ideas, Organize my notes, and Write and say more; POW) before ending intervention (Graham & Harris, 2003).…”
Section: Prior Reviews On Writing Interventions For Students With Iddmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has revealed that people with intellectual disabilities have difficulties reaching certain educational levels, primarily in the field of oral and written communication (Di Blasi et al, 2019 ; Lim & Lee, 2019 ; Ratz & Lenhard, 2013 ; Vega & Gràcia, 2016 ). However, written communication skills have rarely been studied in people with intellectual disabilities, although it is always less developed than oral communication (Banikowski & Mehring, 1999 ; Belva et al, 2012 ; Riaño, 2012 ).…”
Section: Introductionmentioning
confidence: 99%